Fiscal constrains affecting agricultural producer groups - Pieczonka, Jacek (Obciążenia podatkowe grup producentów rolnych, 2012)
The article is aimed at presenting and analysing the principles governing the operations of agricultural producers groups with a special emphasis on corporate income tax obligations. The author will focus on income taxes imposed on the groups’ sales of plant products from their members’ farms as well as on agricultural assets transferred free-of-charge. The article consists of theoretical section presenting definition, objectives and tasks as well as economic environment for agricultural producer groups’ operations and income tax imposed on their sales of plant products, and empirical section presenting: profile of two groups of agricultural producers conducting their activities in Opole Voivodeship including relevant income tax principles
Nauki o Finansach = Financial Sciences, 2012, Nr 1 (10), s. 54-69
Keywords: agricultural producer group; corporate income tax; tax allowances; grupa producentów rolnych; podatek dochodowy od osób prawnych; ulgi podatkowe